Bipolar Disorder : A Guide for Patients and Families - Mondimore, Francis Mark, 1953- (Book collections on Project MUSE., 2006)
Annotation Bipolar disorder can be devastating. It can disrupt relationships and careers, it can wreak havoc on family life, and, when not properly treated, it can be fatal. Since 1999 this compassionate and comprehensive guide has helped tens of thousands of people cope with this complex disease. This, the second edition of Bipolar Disorder, is thoroughly updated and discusses promising new options for diagnosis and treatment along with new information on the disease's genetic components. Bipolar disorder is difficult to diagnose. Dr. Mondimore explains how symptoms fluctuate in persons with seasonal affective disorder, how they can lead to a mistaken diagnosis of attention deficit & ndash;hyperactivity disorder in children, and how they may be made worse by alcohol or drug addiction. The disease can also be difficult to treat. Dr. Mondimore gives advice about how to pick a psychiatrist and cope with the stigma of psychiatric diagnosis. He provides extensive information on treatment options, including the advantages, disadvantages, and side effects of various drug therapies. He also describes what it is like to live with bipolar disorder and discusses how lifestyle changes can improve quality of life. Throughout, he focuses on the importance of building a support system, planning for emergencies, and giving yourself permission to seek help.